Geodesign From Theory to Practice: In the Search for Geodesign Principles in Italian Planning Regulations - Campagna, Michele; Di Cesare, Elisabetta Anna (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Geodesign is a trans-disciplinary concept emerging in a growing debate among scholars in North America, Europe and Asia with the aim of bridging the gap between landscape architecture, spatial planning and design, and Geographic Information Science. The concept entails the application of methods and techniques for planning sustainable development in an integrated process, from project conceptualization to analysis, simulation and evaluation, from scenario design to impact assessment, in a process including stakeholder participation and collaboration in decision-making strongly relaying on the use of digital information technologies. As such, the concept may be not entirely new. However, it is argued here, its application have not reached expected results so far. Hence, more research is needed in order to better understand methodological, technical, organizational, professional and institutional issues for a fruitful application of Geodesign principles and method in the practices. In line with the above assumptions, this paper is aimed at supplying early critical insights as a contribution towards a clearer understanding of the relationships between Geodesign concepts and planning regulations. The auspice with this first endeavour along this research issue is to make a more explicit and robust link between policy principles and planning, design and decision-making methods and tools, possibly as a small contribution to bring innovation in the planning education, governance and practice.